Students’ Gender Proficiency in Multiple Representational Format and Mathematical Reasoning in Senior School Physics Problem-Solving - Funke Susan Apata (Universitas Syiah Kuala, 2022)
This study investigated multiple representation formats and mathematical reasoning to unravel physics concepts and laws in problem-solving. Four hundred and sixty (460) students from forty-six (46) co-educational schools in Kwara State- Nigeria, participated in the study. Using a random sampling technique 230 males and 230 females were selected. The two instruments used are Physics Multiple Representational Test and the Physics Mathematical Reasoning Test. Two research questions and two hypotheses guided the study. Results of the analyses through frequency count, percentages, and t-test revealed a low mean value for mathematical reasoning and the representational format of students. The male recorded a higher mean value in multiple representation formats and mathematical reasoning than their female counterparts. It concluded that students' mathematical reasoning and multiple representational formats in problem-solving were low, and the female students were the most affected when it comes to low performance. The study recommended a curriculum review to accommodate an introductory course on multiple representations. Also, an innovative program that enhances mathematical reasoning and promotes the relationship between mathematics and physics is in the curriculum. Extracurricular activities that could stimulate female interests in representational format and mathematical reasoning, should be introduced in schools.